Interactions of Paraoxonase-1 with Pharmacologically Relevant Carbamates - Anita Bosak (Molecules, 2020)
Mammalian paraoxonase-1 hydrolyses a very broad spectrum of esters such as certain drugs and xenobiotics. The aim of this study was to determine whether carbamates influence the activity of recombinant PON1 (rePON1). Carbamates were selected having a variety of applications: bambuterol and physostigmine are drugs, carbofuran is used as a pesticide, while Ro 02-0683 is diagnostic reagent. All the selected carbamates reduced the arylesterase activity of rePON1 towards the substrate S-phenyl thioacetate (PTA). Inhibition dissociation constants (Ki), evaluated by both discontinuous and continuous inhibition measurements (progress curves), were similar and in the mM range. The rePON1 displayed almost the same values of Ki constants for Ro 02-0683 and physostigmine while, for carbofuran and bambuterol, the values were approximately ten times lower and two times higher, respectively. The affinity of rePON1 towards the tested carbamates was about 3−40 times lower than that of PTA. Molecular modelling of rePON1-carbamate complexes suggested non-covalent interactions with residues of the rePON1 active site that could lead to competitive inhibition of its arylesterase activity. In conclusion, carbamates can reduce the level of PON1 activity, which should be kept in mind, especially in medical conditions characterized by reduced PON1 levels.